AMELIORATIVE EFFECT OF Nigella sativa OIL ON LEAD ACETATE INDUCED HEPATOTOXICITY ON ADULT MALE WISTAR RATS - BALA, USMAN; DAZAR, SAH M.; JIBRIN, MURTALA M; YAKUBU, FATIMA (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2020)
There is an increasing concern about the rising level of lead acetate in environment mainly due to unsafe mining and extraction of natural resource. Several evidences have indicated the devastating effect of the lead exposure to different parts of the body. The Nigella sativa oil is used as natural herbal product for healing of many diseases. Its pharmacological constituents have been shown having anti-oxidant, anti-inflammatory, anti-microbial and anti-parasitic efficacy. This study investigated the ameliorative protective effects of Nigella sativa (black seed) oil on lead acetate induced hepatoxicity in adult male wistar rat. A total number of fourty two rats were divided into six groups of seven rats per group. Group I rats (normal control) were administered normal saline equivalent to the volume administered to the highest dose of treated rats. Group II (negative control)) received 120 mgkg-1of lead acetate while and group III (positive control) received 120 mgkg-1of lead acetate and 160 mgkg-1of vitamin C. Groups IV, V and VI were administered with 120 mgkg-1 of lead acetate followed by 6 mlkg-1, 4 mlkg-1, 2 mlkg-1of Nigella sativa oil respectively via oro-gastric intubation for a period of seven days. The lead acetate caused significant increased (P<0.001) of the liver enzymes (AST, ALT and ALP) in all the negative control groups as compared with the treatment groups, which appeared to be dose dependants. Histopathology observation showed severe liver damage in the lead acetate group. However there is great improvement in the morphology of the liver in the treated groups even at the minimal doses. The changes in the level of biomarkers and improvement in the histomorphological appearance of the liver suggested that, consumption of Nigella sativa oil can be used to ameliorate liver damage.